2016
DOI: 10.3847/0004-637x/825/2/146
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Tagging in the SDSS-Iii/Apogee Survey: New Identifications of Halo Stars With Globular Cluster Origins

Abstract: We present new identifications of five red giant stars in the Galactic halo with chemical abundance patterns that indicate they originally formed in globular clusters. Using data from the Apache Point Observatory Galactic Evolution Experiment (APOGEE) Survey available through Sloan Digital Sky Survey (SDSS) Data Release 12, we first identify likely halo giants, and then search those for the well-known chemical tags associated with globular clusters, specifically enrichment in nitrogen and aluminum. We find tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
103
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 104 publications
(126 citation statements)
references
References 76 publications
22
103
1
Order By: Relevance
“…Considering also the fact that stars with second generation abundances have been found in the halo (e.g., Martell et al 2011;Carretta et al 2010;Carollo et al 2013;Lind et al 2015;Fernandez-Trincado et al 2016), it seems natural to conclude that an association of our N-rich population to the inner halo seems more likely than to the thick disk. The discrepancy with the numbers expected in other regions of the halo (e.g., Martell et al 2011Martell et al , 2016 indicates that the frequency of N-rich stars may be higher in the inner halo, which is in and of itself an important constraint on models for the origin of this population.…”
Section: Bulge Thick Disk or Halo?contrasting
confidence: 62%
See 1 more Smart Citation
“…Considering also the fact that stars with second generation abundances have been found in the halo (e.g., Martell et al 2011;Carretta et al 2010;Carollo et al 2013;Lind et al 2015;Fernandez-Trincado et al 2016), it seems natural to conclude that an association of our N-rich population to the inner halo seems more likely than to the thick disk. The discrepancy with the numbers expected in other regions of the halo (e.g., Martell et al 2011Martell et al , 2016 indicates that the frequency of N-rich stars may be higher in the inner halo, which is in and of itself an important constraint on models for the origin of this population.…”
Section: Bulge Thick Disk or Halo?contrasting
confidence: 62%
“…Adopting the FG/SG ratio from the minimal scenario, the contribution to the halo mass inferred from Martell et al (2011) and Schaerer & Charbonnel (2011) would be reduced by a factor of a few to several. Indeed, in a more recent effort based on APOGEE DR12 data, Martell et al (2016) searched for N-rich stars in high-latitude halo fields adopting a definition that is consistent with that described in Section 2. From a resulting sample of 5 halo N-rich stars, they concluded that, adopting a FG/SG ratio consistent with our minimal scenario, the contribution of dissolved GCs to the halo mass would be ∼4%.…”
Section: Bulge Thick Disk or Halo?mentioning
confidence: 99%
“…The notion is also widely entertained that a substantial loss of stars from GCPs may have been a major contributor to the build up of the stellar halo of the Milky Way and perhaps even of its bulge (Martell et al 2011(Martell et al , 2016Kruijssen 2015;Schiavon et al 2017). Clearly, this possibility opens a direct link between GC formation and the early stages in the formation and evolution of galaxies.…”
Section: Introductionmentioning
confidence: 99%
“…For example, (i) some Aquarius stream stars appear to originate from a GC (e.g., Wylie-de Boer et al 2012); (ii) the Carretta (2013) study on NGC 6752 identifies a few field star candidates with clear chemical patterns of GCs; (iii) Ramírez et al (2012) found an elevated Na/O ratio abundance in two field halo dwarf stars; (iv) Lind et al (2015) recently discovered a metal-poor field halo star with a high Al-Mg ratio; (v) Martell et al (2016) recently identified five stars in the Galactic halo with GC-like abundance patterns, and these stars are thought to be migrants from GCs; (vi) Schiavon et al (2016) analyzed the chemical composition of 5,175 stars in fields centered on the Galactic bulge, and found 59 giant stars with elevated nitrogen abundances, anti-correlated with [C/Fe] and correlated with [Al/Fe] abundance; and several scenarios have been put forward to explain such anomalies in the Galactic bulge, i.e., the authors proposed that these stars may likely come from disrupting GCs, though an alternative scenario being considered is that N-rich stars could be formed in environments similar to GCs (for more details, see Schiavon et al 2016). Detection of such light-element abundance inhomogeneities in non-GC stars is particularly important for understanding how many Galactic field stars could have been deposited by GCs.…”
Section: Introductionmentioning
confidence: 99%